Advantages of the basin approach for investigations of aufeises (naleds) - V. V. Shepelev (Лëд и снег, 2016)
Formation of aufeises (naleds) is rather widely distributed cryogenic process in the permafrost zone, therefore naleds are reasonably called the seasonal glaciation of the planet. The ever-increasing interest in aufeises significantly extends the thematic focus of studying them. Various methodological approaches (basin, geological-structural, lithologic-facies, statistical, etc.) are used to reveal regularities of the aufeis occurrence. Using several river basins in Yakutia and its territory as the examples, the perspectivity of the basin approach for investigation of the aufeis distribution is substantiated in this study. The results demonstrated the clear relationship between the quantitative indicators of areal distribution of naleds and altitudes of places of their formation for individual river basins. This relationship suggests that aufeises in river basins of the permafrost zones are important elements in the water-balance and water exchange, which is closely interrelated with not only climatic and morphometric characteristics of a basin, but it does also correlate with its hydrological, hydrogeological, geological, geocryological, landscape and other conditions.